2022
DOI: 10.3390/children9050631
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Reliability Testing of the Child Oral Impacts on Daily Performances (C-OIDP): Cross-Cultural Adaptation and Psychometric Properties in Pakistani School-Going Children

Abstract: Background: This study aimed to develop an Urdu version of Child-Oral Impact on Daily Performance (C-OIDP) and assess its reliability and validity for children’s oral health-related quality of life (OHRQoL) assessment in Pakistan. Methods: A total of 200 school-going children aged 11–14 were recruited from two public schools. For the adaptation process, the original English version of C-OIDP was translated into Urdu, reviewed by an expert committee, back-translated into Urdu, and then reviewed again by the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
4
6
0
Order By: Relevance
“…Furthermore, the external reliability of index revealed that the value of ICC and weighted kappa were 0.85 and 0.87 respectively, indicated a good agreement. This is consistent with previous studies conducted in United Kingdom and Pakistan [ 8 , 14 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Furthermore, the external reliability of index revealed that the value of ICC and weighted kappa were 0.85 and 0.87 respectively, indicated a good agreement. This is consistent with previous studies conducted in United Kingdom and Pakistan [ 8 , 14 ].…”
Section: Discussionsupporting
confidence: 94%
“…The most impacted daily performances were “eating” and “speaking”, reported by 38.4% and 25.1% of the participants respectively. These results are in line with other studies conducted in Turkey [ 13 ], Nepal [ 10 ] and Pakistan [ 14 ], where “eating” was reported as the most prevalent difficulty. On the other hand, Arumrahayu et al [ 11 ] found that “cleaning teeth” was the most impacted daily performance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It has been used in Mexico to assess the impact of caries and fluorosis in adolescents aged 11 to 12 years [21]. A questionnaire may have good or acceptable reliability in a sample of subjects but not necessarily in another population group or a different region, even in the same country; it is, therefore, desirable to consider the properties [35] and the differential performance of each item. Differences have been observed in responses to items in the FL, SW, and EW dimensions by ethnicity [36].…”
Section: Discussionmentioning
confidence: 99%